Clinical psychology, psychotherapy and psychology students - Meira, Cláudia Hyala Mansilha Grupe; Nunes, Maria Lúcia Tiellet (Paidéia (Ribeirão Preto), 2005)
This article reviews literature concerning psychology students and their interest in clinical psychology and psychotherapy. Freshmen enter the undergraduate course for a psychology degree with a model of clinical psychology and maintain such perspective during the course, following the direction of Brazilian Psychology as a profession. The interest in clinical psychology, in psychotherapy, and in psychoanalysis (in Rio Grande do Sul) directs students to personal psychological treatment which is stimulated by professors and peers, understood as an important tool for personal/professional development. Scielo and PsicInfo as well as journal from the libraries of UFRGS and PUCRS based the literature review.